Sources and levels of endocrine disrupting compounds (EDCs) in Kuwait's coastal areas. Issue 1 (15th May 2017) - Saeed, Talat; Al-Jandal, Noura; Abusam, Abdalla; Taqi, Hameeda; Al-Khabbaz, Ahmad; Zafar, Jamal
Abstract: The sources and levels of endocrine disrupting compounds in Kuwait's coastal areas were investigated. Phthalates, alkylphenols and estrogens were measured in the inflows and outflows of three sewage treatment plants as well as in the seawater and sediments from the sewage impacted coastal areas. Phthalate levels in the inflow of the treatment plants ranged from 8.9 to 78.3 μg/l; alkylphenols from 0.7 to 279 ng/l and estrogens from 30 to 368 ng/l. On average, the treatment plants removed about 80% of these compounds. The outflows, however, contained significant levels of all three classes of compounds. The seawater from the sewage impacted area also contained detectable levels of these compounds. Sediment samples from these locations contained elevated levels of phthalates (ranging from 2145 to 15, 722 μg/kg) and lower levels of alkylphenols (ranging from 2.49 to 15.14 μg/kg) and estrogens (ranging from 4.1 to 214 μg/kg, dry wt.). Highlights: Phthalates, alkylphenols and estrogens determined in treated and untreated sewage. EDCs levels also measured in seawater and sediments from sewage impacted coastal areas. Elevated levels of phthalates found in seawater and sediments.